A study to evaluate the hepatoprotective activity of prebiotics, probiotics, and synbiotic in CCl4 induced hepatotoxicity in rats - Aswad B. Devi,, Anand B. Rahigude, Pradeep B. Parab, Anupama S. Engineer, Prashant K. Dhakephalkar, Kishori G. Apte, (Journal of Applied Pharmaceutical Science, 2021)
The current study was evaluated for the hepatoprotective activity of probiotics, prebiotics alone, and synbiotic of them. Animals were grouped into 12 groups (n = 6), i.e. normal control (NC), disease control (DC), treatment with prebiotics, probiotics alone, and synbiotic of them, and standard marketed hepatoprotective Silymarin along with Synbiotic 2000. All treatments were orally administered daily for 28 days. On the 28th day, all animals except the NC group received carbon tetrachloride (CCl4) (1 ml/kg, i.p.). Levels of serum glutamic pyruvic transaminase (SGPT), serum glutamic-oxaloacetic transaminase (SGOT), alkaline phosphatase (ALP), total bilirubin, total protein, lactate dehydrogenase, and urea were evaluated. The tissues were evaluated for oxidative markers levels of catalase (CAT), lipid peroxidation (LPO), and glutathione (GSH), and total protein. Histopathology of tissues was carried out. Compositional analysis of intestinal microbiota was done by 16S amplicon sequencing. CCl4 caused elevation in SGPT, SGOT, ALP, total bilirubin, urea, and lactate dehydrogenase in the DC group which was prevented with pretreatment of prebiotics, probiotics, and synbiotics. Total protein was decreased in serum and tissues after administration of CCl4 which was restored with pretreatment of test substances. Oxidative marker LPO was increased in the DC group and catalase (CAT) and GSH were also depleted in liver tissue. These changes were prevented in pretreated test groups. The histological change in hepatic parenchyma and hepatocytes was minimal in test groups compared to DC. The 16S amplicon sequencing indicated that Lactobacillus acidophilus and prebiotic treatment effectively displaced Staphylococcus. Results suggested that the use of prebiotics, probiotics alone, and synbiotic of them has a protective effect against CCl4-induced hepatotoxicity in rats.
Keywords: Prebiotics, probiotics, synbiotics, liver toxicity, 16s RNA amplicon, CCl4.